PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DAN MANAJEMEN LABA (Studi pada Perusahaan yang Termasuk dalam LQ-45 Tahun 2011-2013) - Arganata, Jenyarti Dewi; Herawati, Juni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is intent on examining the effect of good corporate governance mechanism (institutional ownership, managerial ownership, board of independent commissioner, and audit committee) toward firm value and earning management at the company that listed in LQ-45 index from 2011 until 2013. The type of this research is hypothesis testing and this research uses multiple regression analysis. The research discovers that firm value is influenced significantly by institutional ownership, managerial ownership, and board of independent commissioner, whereas earning management is only influenced significantly by managerial ownership, and board of independent commissioner. The audit committee in this research has no effect towards both dependent variable, either firm value or earning management. Keywords: good corporate governance mechanism, firm value, earning management.